Sustainable Nature Tourism Business Development in the MICE Industry Era: A Bibliometric Analysis: Asia e University, Malaysia - Hendrata Yudha Wardana; Tulus Suryanto; Juhary Ali (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to investigate the development of scientific research publications related to the development of sustainable natural tourism businesses in the industrial era of meetings, incentives, conferences, and exhibitions (MICE) for the period 2013-2023 on Google Scholar based on keywords and authors using the software Harzing Publish or Perish and VosViewer ver 1.6.20. The findings revealed that out of a total of 1000 searches for international publications with the keyword nature tourism business, only 989 publications were found with the highest total publications in 2013 of 177 publications and the lowest in 2023 of 6 publications. The journal with the highest publication rating is Tourism Management Perspectives with 129 publications. Elsevier Science Publishers is the publisher with the highest publication achievement, namely 307 documents. Cluster 1 in red is the one most associated with the natural tourism business from 2018 to 2023 consisting of 12 items including Airbnb, big data, business analytics, business intelligence, consumer, food, hospitality business, hotel, internet, product, technology, tourist experience, and value. It can be concluded that the development of natural tourism business publications has decreased over the last 10 years. Improvements can be made through research that focuses on MICE activities as shown in the findings regarding the presence of technology keywords. The expected implication is that the results of these findings can contribute to the development of nature tourism business research in the future, especially in looking for references and factors related to this theme